2013
DOI: 10.5296/jmr.v5i2.3266
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financing Pattern and Access to Formal -Informal Credit: The Case of Small and Medium Sized Enterprises in Viet Nam

Abstract: We investigate factors from firm side that determine their financing pattern for new investment projects and their decision to choose formal, informal credit, or both. For financing pattern of new investment project, we use Random-effect model while Unordered-Multinomial Logistic is used to estimate probability of choosing any of four choices to access to finance, say, formal credit, informal credit, both of them, or none of them. Our analysis is based on a panel of around 2200 small and medium sized enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
64
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 28 publications
(16 reference statements)
13
64
2
1
Order By: Relevance
“…Considering most scholars' perspectives on factors influencing SMME borrowing (Berger & Udell 2006;Chandler 2009;Fatoki 2013;Fatoki & Asah 2011;Haron et al 2013;Makhbul 2011;Mutoko & Kapunda 2015;Myers 1984;Nguyen & Luu 2013;Sidik 2012;Zarook, Rahman & Khanam, 2013), the summary of main characteristics that influence borrowing include firm income (net profit or annual turnover) and owner's marital status, gender, highest education qualification and number of years in position.…”
Section: Empirical Literature On the Factors Influencing Small Mediumentioning
confidence: 99%
“…Considering most scholars' perspectives on factors influencing SMME borrowing (Berger & Udell 2006;Chandler 2009;Fatoki 2013;Fatoki & Asah 2011;Haron et al 2013;Makhbul 2011;Mutoko & Kapunda 2015;Myers 1984;Nguyen & Luu 2013;Sidik 2012;Zarook, Rahman & Khanam, 2013), the summary of main characteristics that influence borrowing include firm income (net profit or annual turnover) and owner's marital status, gender, highest education qualification and number of years in position.…”
Section: Empirical Literature On the Factors Influencing Small Mediumentioning
confidence: 99%
“…In addition, several research on access to informal credit in Vietnam such as Tarp. F. (2008), Rand (2009), Nguyen and Luu (2013) for instance, did not exclude it out of the sample as we expected too. Hence, in this paper, we exclude firms that consider family as the most important informal credit source in order to explore new determinants of access to informal credit for Vietnamese SMEs.…”
Section: Literature Reviewmentioning
confidence: 89%
“…With regards to the determinants of access to informal credit, factors such as formal credit constraints, age and size of firms, firm performance, location, owner characteristics have been discussed (Safavian and Wimpey, 2007;Rand, 2009;Yaldiz et al 2010;Nguyen and Luu, 2013;Madestam, 2014;Yener, 2014). In an effort to investigate the impact of a firm's usual environment on firms' access to informal credit market, Safavian and Wimpey (2007) analyzed the link between corruption, regulation and financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Age: The age of the applicant is another commonly studied factor in the field [29] no evidence of age bias has been provided. However, Nguyen and Luu [27] and Abdulsaleh and Worthington [30], among others, found that age does have an effect on the capability to succeed in loan issuance. Race: Racial discrimination in the field of credit allocation has been analyzed several times in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%